Oral administration of Lactobacillus fermentum CRL1446 improves biomarkers of metabolic syndrome in mice fed a high-fat diet supplemented with wheat bran - Russo, Matias Irineo (2020)
This work aimed to evaluate the effect of oral administration of probiotic Lactobacillus (L.) fermentum CRL1446, with feruloyl esterase (FE) activity, on metabolic biomarkers and intestinal microbiota of mice with high fat diet-induced Metabolic Syndrome (MS) and supplemented with wheat bran as a source ofesterified ferulic acid. Six-week-old male Swiss albino mice developed the components of MS when fed with high fat diet supplemented with wheat bran (HFD + WB) for 14 weeks. Positive impact of L. fermentum CRL1446 administration on these animals was reflected in a decrease in body weight gain and adiposity index compared to the animals that did not receive the probiotic strain. In addition, a decrease in plasma leptin levels, improvement of inflammatory profile, reduction of fatty infiltration in hepatocytes and modification of lipid profile (increased HDL-cholesterol and decreased LDL-cholesteroland triglyceride levels) were observed. On the other hand, L. fermentum CRL1446 reduced fasting glucose and insulin levels, improving the HOMA index in mice with MS. Postprandial glucose levels were also reduced in the oral glucose tolerance test. Consumption of L. fermentum CRL1446 with HFD + WB (HFD + WB-Lf mice group) had a great impact on host metabolism, modulating intestinal microbiota, with an increase in Bacteroidetes and a decrease in Firmicutes abundance being observed. Increased intestinal FE activity, improved oxidative status and increased abundance of 3-hydroxyphenylpropionic acid andbutyric acid concentration in colonic content, were also demonstrated in HFD + WB-Lf mice. Results obtained suggest that supplementation with L. fermentum CRL1446 enhances beneficial effects of a bran diet, attenuating the risk factors associated with MS.